Hemostatic assessment, treatment strategies, and hematology consultation in massive postpartum hemorrhage: results of a quantitative survey of obstetrician-gynecologists - James AH; Cooper DL; Paidas MJ (Dove Medical Press, 2015)
Andra H James,1 David L Cooper,2 Michael J Paidas31Department of Obstetrics and Gynecology, Division of Maternal-Fetal Medicine, Duke University, Durham, NC, 2Novo Nordisk Inc., Princeton, NJ, 3Department of Obstetrics, Gynecology, and Reproductive Sciences, Yale Women and Children’s Center for Blood Disorders and Preeclampsia Advancement, Yale University, New Haven, CT, USAObjective: To assess potential diagnostic and practice barriers to successful management of massive postpartum hemorrhage (PPH), emphasizing recognition and management of contributing coagulation disorders.Study design: A quantitative survey was conducted to assess practice patterns of US obstetrician-gynecologists in managing massive PPH, including assessment of coagulation.Results: Nearly all (98%) of the 50 obstetrician-gynecologists participating in the survey reported having encountered at least one patient with “massive” PPH in the past 5 years. Approximately half (52%) reported having previously discovered an underlying bleeding disorder in a patient with PPH, with disseminated intravascular coagulation (88%, n=23/26) being identified more often than von Willebrand disease (73%, n=19/26). All reported having used methylergonovine and packed red blood cells in managing massive PPH, while 90% reported performing a hysterectomy. A drop in blood pressure and ongoing visible bleeding were the most commonly accepted indications for rechecking a “stat” complete blood count and coagulation studies, respectively, in patients with PPH; however, 4% of respondents reported that they would not routinely order coagulation studies. Forty-two percent reported having never consulted a hematologist for massive PPH.Conclusion: The survey findings highlight potential areas for improved practice in managing massive PPH, including earlier and more consistent assessment, monitoring of coagulation studies, and consultation with a hematologist.Keywords: acquired hemophilia, blood coagulation disorders, disseminated intravascular coagulation, von Willebrand disease